2017
DOI: 10.1108/ijqss-02-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality performance between public and private hospitals in Malaysia

Abstract: For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
(24 reference statements)
1
16
0
Order By: Relevance
“…However, there is currently no comparable standard assessment of patient satisfaction or experience in Malaysia’s public or private hospitals. While the MOH favors the SERVQUAL questionnaire, private hospitals may develop their own surveys or use another international standard [ 55 , 56 ]. Thus, Facebook reviews may serve as a new standard of patient satisfaction in both the public and private sectors.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is currently no comparable standard assessment of patient satisfaction or experience in Malaysia’s public or private hospitals. While the MOH favors the SERVQUAL questionnaire, private hospitals may develop their own surveys or use another international standard [ 55 , 56 ]. Thus, Facebook reviews may serve as a new standard of patient satisfaction in both the public and private sectors.…”
Section: Discussionmentioning
confidence: 99%
“…TQM is a multidimensional construct (Samson and Terziovski, 1999; Kaynak, 2003; Khalaf and Salem, 2018). The most commonly studied dimensions of TQM in health-care organizations are leadership, management commitment, human resources management, strategic quality planning employee involvement quality data and reporting, process management, supplier quality management, continuous improvement product/service design, training and development, quality and organizational culture, customer focus, teamwork, organizational structure, benchmarking, knowledge management, work environment (Øvretveit,2000; Mosadeghrad, 2014a; Sweis et al , 2016; Ahmed et al , 2017; Oliveira et al ,2019; Wang et al ,2019; Babu and Thomas, 2020). A meta-analytic study done by Mosadeghrad (2014a) identified 52 TQM practices from 37 empirical studies about TQM practices in the health-care sector and found that management leadership, human resource management, customer focus, process management, information and analysis and supplier quality management were the most commonly used dimensions of TQM.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The impact of adopting TQM practices on various aspects of the hospital performance is studied in western literature (Sabella et al , 2014; Ju and Park, 2016; Sweis et al , 2016); Ahmed et al , 2017; Kanapathy et al , 2017; Modgil and Sharma, 2017; Oliveira et al , 2019). However, many studies on TQM practices highlighted that there are considerable differences in the benefits of implementing quality management practices between manufacturing and service sectors and its implementation is not always successful in service organizations (Kaynak, 2003; Gupta et al , 2005; Rönnbäck and Witell, 2008; Khalaf and Salem, 2018; Oliveira et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al (2017) found that Malaysian citizens, irrespective of educational background and income bracket, are spending a substantial yet soaring amount of money on medical services in both private and public hospitals.…”
Section: Introductionmentioning
confidence: 99%